2016
DOI: 10.1084/jem.20150577
|View full text |Cite
|
Sign up to set email alerts
|

BAFF-secreting neutrophils drive plasma cell responses during emergency granulopoiesis

Abstract: Harris and collaborators show that neutropenia results in increased formation of plasma cells and elevated antibody production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 50 publications
(66 reference statements)
5
74
1
Order By: Relevance
“…In this regard, BAFF can act as a co-stimulatory molecule for T-cells and promote Th17 development (268, 269). BAFF can also directly activate plasma cells, which are not depleted by rituximab (270, 271). …”
Section: T1-ifns the Th17 Response And Their Interactions In Autoimmmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, BAFF can act as a co-stimulatory molecule for T-cells and promote Th17 development (268, 269). BAFF can also directly activate plasma cells, which are not depleted by rituximab (270, 271). …”
Section: T1-ifns the Th17 Response And Their Interactions In Autoimmmentioning
confidence: 99%
“…Thirdly, T1-IFNs stimulate BAFF production, which is essential for T1-IFN-mediated pathogenic effects in mouse SLE (261, 262, 293). It is recently shown that IL-17 also induces BAFF production and that IL-17-driven, G-CSF-dependent PMN recruitment drives plasma cell responses during emergency granulopoiesis in a BAFF-dependent way (271). Also, therapeutically administered G-CSF, which is physiologically induced by IL-17, increases BAFF production by PMN (294).…”
Section: T1-ifns the Th17 Response And Their Interactions In Autoimmmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the absence of IL-17R signaling could alter the activity of neutrophils recruited to the spleen after infection. A recent study has identified that IL-17 stimulated prostaglandin E2 production by stromal cells recruits BAFF-producing neutrophils to support B cell activation and survival (55). As we observed a decrease in expression of Cox2 , which promotes prostaglandin synthesis, by FRCs from Il-17ra −/− mice after infection, this could result in a decline in BAFF production by recruited neutrophils, leading to a subsequent decline in B cell numbers, specifically activated B cells undergoing plasmablast differentiation.…”
Section: Discussionmentioning
confidence: 99%